The autogenous graft versus transport distraction osteogenesis for reconstruction of the ramus–condyle unit: a prospective comparative study. Issue 9 (September 2017) - Kohli, S.; Mohanty, S.; Singh, S.; Sandeep,; Dabas, J.; Patel, R.
Abstract: This study aimed to compare the joint function and morphology achieved following condylar reconstruction using sternoclavicular grafts (SCG) versus transport distraction osteogenesis (TDO) in temporomandibular joint (TMJ) ankylosis patients. Twenty-two patients with TMJ ankylosis underwent TMJ reconstruction with SCG or TDO ( n = 11 each). Radiographic and clinical evaluations were performed at 1 week and at 1, 3, and 6 months post-surgery. Clinical criteria examined included the duration of surgery, mean postoperative mouth opening, excursive jaw movements, and pain scores. The radiographic evaluation 6 months postoperatively (computed tomography) included subjective assessment of joint morphology and measurements of the mean condylar height, width achieved, and amount of condylar resorption. The χ 2 test and Student t -test were used to compare qualitative and quantitative variables, respectively. Similar mean mouth opening (SCG = 31.8 mm, TDO = 32.1 mm at 6 months), excursive movements, and pain scores were observed in the two groups throughout follow-up. Mean condylar resorption was significantly greater in the TDO group (TDO = 7.0 mm, SCG = 2.7 mm; P = 0.005). The duration of reconstruction surgery was greater in the SCG group ( P = 0.035). A greater incidence of complications was observed with TDO. In conclusion, based on the protocols used in this study, SCGs are superior to TDO in terms of condylar morphology, stability, and surgical safety.